2018
DOI: 10.1002/star.201700213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Precipitation Conditions on Crystallinity of Amylose Nanoparticles

Abstract: Amylose nanoparticles are prepared via precipitation by dropping absolute ethanol into amylose paste. X‐ray diffraction analysis reveales that the amylose nanoparticles display V‐type crystalline structure, and crystallinity of the amylose nanoparticles is dependent upon precipitation conditions, that is, temperature of amylose paste, ethanol dropping rate, and length of amylose chains. Dropping ethanol of 20 °C into amylose paste of 90 °C at a rate of 5 mL min−1 promotes the molecular association of amylose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Particle size distribution of the starch‐lutein nanoparticles was analyzed according to previously reported method . Dispersion (0.05% w/v) of starch‐lutein nanoparticles (after drying) in deionized water was prepared, the analysis was carried out by using a Malvern Zetasizer Nano‐ZS90 (Malvern Instruments Ltd., UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle size distribution of the starch‐lutein nanoparticles was analyzed according to previously reported method . Dispersion (0.05% w/v) of starch‐lutein nanoparticles (after drying) in deionized water was prepared, the analysis was carried out by using a Malvern Zetasizer Nano‐ZS90 (Malvern Instruments Ltd., UK).…”
Section: Methodsmentioning
confidence: 99%
“…The X‐ray diffraction patterns were recorded over the 2 θ range of 4–35° with a speed of 2° min −1 . Crystallinity of the starch‐lutein nanoparticles was calculated by using previously described method …”
Section: Methodsmentioning
confidence: 99%
“…Chemical reagents are usually used to modify the performance of starch; however, homogeneously mixing these reagents with starch to permeate its internal structure is difficult. Therefore, more highly efficient methods by which starch can be modified have recently been the subject of attention and are showing great potential . To that end, microwaves, a type of electromagnetic wave, can heat reactants without conducting that heat, accelerate the reaction rate of the thermal effect from internal expansion, and improve the contact between the starch and the reagent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, B‐type, A‐type, and V‐type amylose were obtained from pure water, 15% (v/v) ethanol and 40% (v/v) ethanol, respectively . On the other hand, crystallinity was often observed in the starch nanoparticles which were prepared by adding an excess of anhydrous ethanol into the starch solution …”
Section: Introductionmentioning
confidence: 99%
“…[9] On the other hand, crystallinity was often observed in the starch nanoparticles which were prepared by adding an excess of anhydrous ethanol into the starch solution. [13,14] It was found that polyethylene glycol (PEG) could precipitate dextrin like ethanol. [15,16] In addition, crystalline starch microspheres were successfully prepared in an aqueous two-phase system formed by starch and PEG.…”
Section: Introductionmentioning
confidence: 99%